The angels' share [compact disc, unabridged] : a Bourbon kings novel - Ward, J. R., 1969- (Ward, J. R., 1969- Bourbon kings novel., 2016)
When the apparent suicide of the Bradford family patriarch starts to look more and more like murder, no one is above suspicion - especially the eldest son, Edward. As the investigation into the death intensifies, he keeps himself busy at the bottom of a bottle - and with two women who may or may not have his best interests at heart. Then, at the very brink of the family's demise, with their bourbon business on the brink of financial ruin, someone thought lost to them forever returns to the fold. Maxwell Bradford has come home. But is he a savior - or the worst of all the sinners?